The U.S. intelligence community - Richelson, Jeffrey (Westview Press, 2016)
"The role of intelligence in U.S. government operations has changed dramatically and is now more critical than ever to domestic security and foreign policy. This authoritative and highly researched book written by Jeffrey T. Richelson provides a detailed overview of America's vast intelligence empire, from its organizations and operations to its management structure. Drawing from a multitude of sources, including hundreds of official documents, The U.S. Intelligence Community allows students to understand the full scope of intelligence organizations and activities, and gives valuable support to policymakers and military operations. The seventh edition has been fully revised and updated to include revamped chapters on signals intelligence and cyber collection, geospatial intelligence, and open sources and exploitation. The inclusion of more maps, tables and photos makes it an even more valuable and engaging resource for students. In addition, a new web site provides access to the documents referenced in the book and suggestions for supplementary case studies"--
Keywords: Intelligence service : United States